Epicardial adipose tissue and adrenal gland volume in patients with borderline personality disorder. (December 2021) - Richter, A.; Stapel, B.; Heitland, I.; Westhoff-Bleck, M.; Ponimaskin, E.; Stubbs, B.; Lichtinghagen, R.; Hartung, D.; Kahl, K.G.
Abstract: Borderline personality disorder (BPD) is associated with an elevated mortality risk that is partially attributed to suicide, but few studies examined other possible causes of premature death. The present study compared epicardial adipose tissue (EAT) volume as a known early predictor of premature cardiovascular morbidity, cardiovascular risk indices, and adrenal gland volume (AGV) as an indicator for chronic hypothalamus-pituitary-adrenal (HPA) axis activation in females with borderline personality disorder (BPD), major depressive disorder (MDD) and in healthy individuals. Twenty-eight patients with BPD comorbid with MDD (BPD/MDD), 22 MDD patients and 26 healthy females (CTRL) of comparable age were included. EAT and AGV were assessed by magnetic resonance tomography; 10-year cardiovascular risk and diabetes risk were determined by PROCAM and FINDRISK score; metabolic syndrome was defined following National Cholesterol Education Adult Treatment Panel III R (NCEP/ATP III) criteria. MADRS was used to assess depression severity. After adjustment for age, body mass index (BMI), and physical activity, EAT and AGV were significantly increased in BPD/MDD compared to MDD and CTRL. EAT and AGV displayed a positive correlation. Finally, diabetes risk in BPD/MDD was elevated compared to CTRL and MDD. The present study highlights the increased cardiometabolic risk of BPD patients. We identify EAT accumulation as an early predictor and potential mediator of cardiovascular disease in BPD that appears to be driven at least in part by HPA axis dysregulation. Therefore, interventions that reduce EAT volume (i.e. exercise and diet) should be considered in the clinical management of BPD.